Co-optimization of the shape, orientation and layout of offshore wind farms. Issue 4 (September 2020) - Feng, Ju; Shen, Wen Zhong
Abstract: Previous studies on wind farm design optimization usually assume that the wind farm boundary is fixed. However, due to the uneven distribution of energy for different wind directions, the wind farm boundary, which determines the possible shape and orientation of the wind farm, can have large influences on the wind farm's energy production. Towards an overall design optimization, the shape and orientation of wind farm should also be considered as part of the design variables. To tackle this problem, we formulate a co-optimization problem of the wind farm's shape, orientation and layout to maximize AEP under several realistic constraints. As an initial effort, we limit the wind farm boundary to parallelogram shapes. A two-stage optimization method is then proposed to solve the co-optimization problem. The case study on the Horns Rev 1 offshore wind farm demonstrates the importance of choosing proper shape and orientation and the effectiveness of the proposed optimization method.